PENGARUH PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2016-2018) - Izza Noor Fauziah; Bambang Sudiyatno (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
This study aims to examine and find out how the influence of profitability and company growth on the firm value with capital structure as a moderating variable. This research was conducted at the Indonesia Stock Exchange using an analysis unit of manufacturing companies. This sampling method uses a purposive sampling method that is 255 companies with a research period in 2016-2018. The relationship or influence on these variables is explained by using the multiple regression analysis method. The results showed that profitability had a positive and significant effect on firm value, company growth had a negative and significant effect on firm value, capital structure was able to moderate the effect of profitability on firm value, capital structure was able to moderate the effect of company growth on firm value. Keywords: profitability, company growth, capital structure, firm value